BNCC Arte: entre o sonho neoliberal e o governo da alma - Ferreira, Rafael Vicente [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
A Base Nacional Comum Curricular (BNCC) é um documento normativo que redefine os parâmetros da educação em todo território nacional, partindo de uma progressão de aprendizagens essenciais ancoradas em competências e habilidades. Na presente dissertação, a discursividade desse documento é investigada, tendo como enfoque o componente curricular Arte, envolvendo suas Unidades Temáticas (Artes Visuais, Dança, Música, Teatro e Artes Integradas) e a Área de Linguagens. Junto com a investigação da Base, outras discursividades relacionadas são cotejadas, com especial destaque para as transformações no Programa Nacional do Livro e do Material Didático (PNLD) a partir da BNCC. A abordagem teórico-metodológica parte de um encontro entre os repertórios foucaultiano e marxista, com destaque para os processos de objetivação e subjetivação, determinados pela ideologia neoliberal hegemônica. Por fim, são indicados possíveis caminhos para “hackear” a BNCC Arte: construir a partir do próprio documento currículos críticos de arte/educação.

The Brazilian Common Core Curriculum [BNCC] is a normative document that redefines educational parameters for the entire nation, based on the progressive acquisition of essential learning competencies and abilities. Discourse analysis of this document is undertaken in this dissertation, focusing specifically on the Art component of the curriculum, involving its Thematic Units (Visual Arts, Dance, Music, Theater, and Integrated Arts) as well as the Area of Languages. In conjunction with the Common Core Curriculum, other discourses related to it are investigated, with special emphasis on the transformations it brought about within the Brazilian National Book and Didactic Material Program (PNLD). The theoretical and methodological framework of the analysis undertaken herein is based on an encounter between Marxist and Foucauldian repertoires, with special emphasis on processes of subjectification and objectification, determined by hegemonic neoliberal ideology. Finally, possible routes for “hacking” the Arts section of the BNCC are indicated: pathways for building critical art/education curricula based on the document itself.
The Brazilian Common Core Curriculum [BNCC] in Art: between the neoliberal dream and the government of the soul
Keywords: Arte/Educação; Artes; Currículo; Educação; Ensino de arte; Política educacional; Neoliberalismo; BNCC; PNLD; Art/Education; Art teaching; Arts; Curriculum; Education; Educational politics; Neoliberalism